Gender-responsive development: Opportunities for co-operation between the African Union, its member states and Denmark - Karmen Tornius; Lars Engberg-Pedersen (Danish Institute for International Studies (DIIS), 2023)
To examine possible common ground for co-operation between certain African countries, the African Union (AU) and Denmark, this study reviews the gender equality priorities of the AU and nine of its member states. The study explores (I) the priorities, contestations and gaps in the AU's gender governance; (II) the status of and priorities in gender-responsive governance at country level; and (III) African priorities in global gender policy spaces. Noting AU's focus on harmful (traditional) practices, women, peace and security, sexual and reproductive health and rights and women in decision-making, there are opportunities to build on this existing work. A closer look at some member states shows that countries' engagement with gender equality issues is shaped by their internal stability, changes in political regime and approach to governance. At the global governance level, not all countries participate equally and the Africa Group rarely participates with a common voice.
Keywords: 330; Gender equality; fragile states; the Third Committee; African Union; Danish development co-operation; Denmark